Peran Inspektorat sebagai Aparat Pengawas Intern Pemerintah (APIP) dalam Mewujudkan Good Governance pada Kabupaten Lanny Jaya - Oktovianus Seba; Abner Herry Bajari; Ari Juliana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the role of the Inspectorate as the Government Internal Supervisory Apparatus (APIP) in realizing good governance in Lanny Jaya Regency, particularly in supervising the management of regional finances and village funds. The research method used is a qualitative method with a descriptive approach, through data collection techniques in the form of in-depth interviews, observations, and documentation of 28 informants, and analyzed using the help of N-Vivo software through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the role of APIP in realizing good governance is demonstrated through the application of ethics and organizational values ​​such as integrity, honesty, responsibility, and accountability, as well as through risk-based audit performance management that includes audit planning, risk communication, activity coordination, and resource management. However, there are still obstacles in the form of weak risk communication, lack of information transparency, limited resources, and suboptimal coordination with external parties that have an impact on the continued occurrence of irregularities in the management of village funds. The conclusion is that the role of the Inspectorate as APIP has been running but is not optimal, so it is necessary to strengthen the risk-based supervision aspect, improve the quality of human resources, as well as transparency and coordination to realize good governance effectively. Keywords: Good Governance, Supervision, Risk-Based Audit, Inspectorate